The SPOP-ITCH Signaling Axis Protects Against Prostate Cancer Metastasis - Ma, Jinlu; Cai, Mengjiao; Mo, Yaqi; Fried, Joshua S.; Tan, Xinyue; Ma, Yuan; Chen, Jie; Han, Suxia; Xu, Bo (Frontiers in Oncology, 2021)
Prostate cancer is one of the most common causes of cancer incidence and death in men, with the mortality caused primarily by the late-stage and metastatic forms of the disease. The mechanisms and molecular markers for prostate cancer metastasis are not fully understood. Speckle type Poz Protein (SPOP) is an E3 ubiquitin ligase adaptor that is often mutated in prostate cancer. In this study, we sequenced the SPOP gene in 198 prostate cancer patients and found 16 mutations in the cohort. Multivariate analysis revealed that SPOP mutations correlated with the clinical stage of the disease and strongly with metastasis. We identified ITCH as a candidate protein for SPOP-mediated degradation via mass spectrometry. We demonstrated the interaction between SPOP and ITCH, and found that the SPOP F133L mutation disrupted the SPOP-ITCH interaction, leading to a subsequent increase in the ITCH protein level. Further, we found that the SPOP knockdown led to higher levels of Epithelial- mesenchymal transition (EMT) proteins and increased cell invasion. Together, our results highlight the functional significance of the SPOP-ITCH pathway in prostate cancer metastasis.